2017
DOI: 10.1111/liv.13525
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the 24‐hour rhythm of skin temperature in cirrhosis: Sleep‐wake and general clinical implications

Abstract: Alterations of distal/proximal skin temperature, their gradient and their time-course were observed in patients with cirrhosis, which may contribute to their sleep disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 38 publications
5
34
2
Order By: Relevance
“…Additionally, as recent studies have showed thermoregulatory impairment in cirrhotic patients both in skin temperature recordings and core body temperature readings (30,31).…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, as recent studies have showed thermoregulatory impairment in cirrhotic patients both in skin temperature recordings and core body temperature readings (30,31).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, there are other markers that can be easily measured and that can reflect circadian phases as well, such as the core body temperature, melatonin, and cortisol secretion (reviewed in Evans & Davidson, 2013). Several recent studies have selected body temperature as a determinant parameter for circadian rhythm evaluation (Garrido et al, 2017;Martinez-Nicolas et al, 2018). Body temperature can be easily measured through wristbands, usually in the non-dominant arm.…”
Section: Monitoring Of Circadian Rhythms In Humansmentioning
confidence: 99%
“…
We recently reported that patients with cirrhosis exhibit an abnormal pattern in their skin temperature variability, with complexity analysis of skin temperature fluctuations distinguishing inpatients from outpatients, despite similar mean temperature values [1]. Patients with cirrhosis also exhibit abnormalities in circadian rhythmicity, part of which are of central origin [2].
…”
mentioning
confidence: 99%